Pertanggung Jawaban Pribadi Dan Jabatan Dalam Hukum Administrasi Negara - Abdul Basid Fuadi (UIN Sunan Kalijaga Yogyakarta, 2020)
The modern state is the personification of the legal system so that almost all countries in the world claim to be a state of law. However, the paradigm of the rule of law idea has shifted to the concept of a welfare state. This is because to carry out a government with increasingly complex needs of society is not sufficient only by referring to the legislative delegation or implementing laws. It is in this framework that the government is then given the authority to act on its own initiative in solving problems faced by society in the form of discretion. The problem is how to be accountable when the authority essentially contains responsibility consequences, the problem that arises next is that every government administration is always carried out by two entities, namely positions (government) and officials (people) as individuals who carry out government affairs. This paper finds that if there is an element of administrative error that causes loss to citizens, the responsibility and accountability will be borne by the person of the perpetrator of the maladministration, both administratively and even turning into a criminal responsibility.Negara modern adalah personifikasi tata hukum sehingga hampir seluruh negara di dunia mengklaim diri sebagai negara hukum. Namun paradigma gagasan negara hukum telah bergeser kepada konsep negara kesejahteraan. Sebab untuk menyelenggarakan pemerintahan di ruang publik yang semakin kompleks tidak cukup hanya dengan berpedoman pada delegasi undang-undang atau melaksanakan undang-undang. Dalam kerangka inilah kemudian kepada pemerintah diberikan wewenang bertindak dengan inisiatif sendiri dalam menyelesaikan persoalan-persoalan yang dihadapi masyarakat berupa diskresi. Permasalahannya adalah bagaimana pertanggungjawabannya ketika wewenang pada hakikatnya mengandung konsekuensi pertanggungjawaban, problematika yang muncul berikutnya adalah setiap penyelenggaraan pemerintahan selalu dilakukan dua entitas, yaitu jabatan (pemerintah) dan pejabat (orang) sebagai pribadi yang menjalankan urusan pemerintahan. Tulisan ini menemukan jika terdapat unsur kesalahan administrasi yang menyebabkan kerugian warga negara, tanggung jawab dan tanggung gugatnya dibebankan pada pribadi pelaku tindakan maladministrasi tersebut, baik secara administratif bahkan bisa berubah menjadi tanggung jawab pidana.